THE EFFECTIVENESS OF USING TALAQQI AND FLASHCARD METHODS IN LEARNING HIJAIYAH LETTERS FOR EARLY CHILDREN IN CIKARET VILLAGE - Adhha Sya’roni, Muhammad Asyrul; Kasman, Rusdi (LPPM Univ. Ibn Khaldun Bogor, 2022)
Learning to recognize hijaiyah letters is very important for early childhood and needs to be taught with learning methods and media that are adapted to the child's developmental stage. Given the many phenomena in today's society, children have little ability to memorize, remember and recognize hijaiyah letters. The facts also factor from the child's own will, the lack of facilities to the lack of guidance from parents. Based on the existence of this article, it is hoped that it can help a lot to facilitate parents, teachers or anyone who wants to teach hijaiyah letters. The use of effective media and methods in learning to recognize hijaiyah letters by using the tallaqi and flashcard methods, because it has its own advantages. This research was conducted by conducting observations, interviews, and documentation. This research was conducted in Madrasah Diiniyah Takmiiliyyah Nurul Ummah, Cikaret GG.R Kosasih Rt 06/08 Cikaret Village, South Bogor District. The type of research conducted is descriptive qualitative research, with the target of two study groups in children aged 2-5 and 6-10 years. documentation and literature study so as to produce a research type descriptive qualitative research. The results of this study indicate that the learning model of hijaiyah letters using flashcards and tallaqi in Cikaret village is able to increase interest in learning and satisfying results, and children are not bored in learning.